Cloning, sequencing, and regulation of expression of an extracellular esterase gene from the plant pathogen Streptomyces scabies. - Raymer, G (1990)
The gene that encodes the extracellular esterase produced by Streptomyces scabies has been cloned and sequenced. The gene was identified by hybridization to a synthetic oligonucleotide that corresponds to the amino-terminal amino acid sequence determined for the secreted form of the esterase. Nucleotide sequence analysis predicted a 345-amino-acid open reading frame, a putative ribosome-binding site, and 39 amino acids at the amino terminus of the sequence that is not found in the secreted protein. This 39-amino-acid sequence has many of the characteristics common to known signal peptides. End mapping the esterase transcript revealed a single 5' end of the mRNA located 51 nucleotides upstream from the start point for translation. Northern (RNA) hybridization analysis of the esterase message by using the cloned esterase gene as a probe indicated that the esterase mRNA is about 1,440 nucleotides in length and was detected only when the cells were grown in the presence of zinc. These results suggest that the level of esterase mRNA detected in the cells is regulated by zinc.